Respect in intergenerational relationships: Young adult women's motivations: Research. Issue 1 (2nd January 2019) - van Biljon, Lizanlé; Roos, Vera; O'Reilly, Susan
ABSTRACT: Care and respect are two sides of the same coin, yet very little is known about respect shown by younger women in relation to people aged 60 and older. This study sets out to explore what motivates young adult women to respect older people. Twenty-five post-graduate women from a tertiary education institution in South Africa participated in the Mmogo-method®, a projective visual data-collection method, to produce textual and visual data. These were analysed using sequential and visual analysis. Findings reported combinations of motivational types for respect of older people, on a continuum from extrinsic (socialised normative values) to intrinsic (personal choice and empathy), and from conditional to unconditional, namely: extrinsic/conditional; extrinsic/unconditional; self-motivated/conditional and self-motivated/unconditional. Respect as an impact on relational interactions between people is either constructive and encouraging or damaging and disparaging. Interpersonal risks are associated with motivation and this could affect future interactions and manifestations of intergenerational respect.